EXPLORING THE RHETORICAL STRUCTURES IN UNDERGRADUATE THESIS INTRODUCTIONS: A GENRE ANALYSIS - Mustaqim, Muhammad Haris; Sylvia, Rizka (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The introduction section of a thesis or research paper serves as a critical foundation, providing readers with a clear understanding of its objectives, context, and significance. This study aims to analyze the rhetorical structure of introduction sections in undergraduate theses to identify patterns and variations in their construction. Specifically, the research investigates the use of Swales’ revised Create-A-Research-Space (CARS) model in 10 undergraduate theses from two universities. This qualitative analysis uses a dataset randomly selected from a larger corpus, combining Swales’ CARS model with frequency analysis of moves and steps, as described by Kanoksilapatham (2005). The findings reveal consistent application of Moves 1, 2, and 3, although the frequency of specific steps varies. Moreover, all writers demonstrated appropriate sequencing of moves and steps, aligning with the CARS framework. These results aim to provide valuable insights for academic writing pedagogy, particularly for English as a Foreign Language (EFL) instructors, in helping students develop effective thesis introductions. Additionally, the findings contribute to enhancing EFL students' skills in writing well-structured introductions and increasing researchers’ competency in crafting coherent and impactful introductory sections.